PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH TERHADAP PRESTASI BELAJAR AKUNTANSI PERUSAHAAN JASA SISWA PROGRAM KEAHLIAN AKUNTANSI KELAS X DAN XI DI SMK KANSAI PEKANBARU - Suci Hendristiana; Gimin '; Rr.Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the influence of school environment and school environment on student accounting learning achievement of accounting services program students class X and XI in SMK Kansai Pekanbaru. The population in this study are students of accounting skills program class X and XI with total 66 students, and all students become subject of research, so this research is population research. Measurement of data using questionnaires and documentation. Data analysis used is multiple linear regression. The result of the research based on multiple linear regression shows the environment of family and school environment have an effect on student accounting achievement of student service program of accountancy skill class X and XI in SMK Kansai Pekanbaru, this can be seen from constanta value (a) equal to 39,497, regression coefficient value (b ) Equal to 0,260, and regression coefficient (c) equal to 0,554 with regression equation 39,497+ 0,260 LK + 0,554 LS. Judging from the calculation of R2 (R Square Change) obtained value of 0.434. This means that the percentage of contribution of family environment and school environment influences on learning achievement variable is 43.4%. Based on these results suggested that students are expected to have good learning habits, always motivate themselves to not easily affected by the circumstances and the environment around so as to remain concentrated in education and in achieving better learning, from the family, especially in this case parents, Is expected to give great attention to the child in learning. Attention is not only in the form of providing adequate learning facilities for children at home but also psychological attention so that children are more concentrated in learning and can achieve better learning achievement, school should be able to keep the situation and conditions of learning remain conducive for students comfortable in learning. Schools also need to improve the quality and quantity of learning facilities that support teaching and learning activities along with good management, teachers as facilitators should be able to create a more enjoyable environment and learning environment for students. Teachers need to vary the use of learning methods to improve students' attention and motivation in learning.Keywords: Family environment, School environment, Learning achievement